Axis formation during Drosophila oogenesis. - Riechmann, V.; Ephrussi, A. (Current Opinion in Genetics and Development, 2001)
Recent advances shed light on the cellular processes that cooperate during oogenesis to produce a fully patterned egg, containing all the maternal information required for embryonic development. Progress has been made in defining the early steps in oocyte specification and it has been shown that progression of oogenesis is controlled by a meiotic checkpoint and requires active maintenance of the oocyte cell fate. The function of Gurken signalling in patterning the dorsal-ventral axis later in oogenesis is better understood. Anterior-posterior patterning of the embryo requires activities of bicoid and oskar mRNAs, localised within the oocyte. A microtubule motor, Kinesin, is directly implicated in localisation of oskar mRNA to the posterior pole of the oocyte.